Prediction and validity of maximal aerobic power for South Korean male by metabolic responses in submaximal exercise and distance running - Im, J. H.; Jeon, Y. J.; Chang, H. K.; Kim, H. J.; Kim, K. H.; Lee, B. K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purpose of this study was to develop the prediction model of maximal aerobic power or South Korean Male by submaximal metabolic responses from treadmill exercise (Bruce protocol) and general physical variables, and to compare and analyse the validity of these prediction models. The purpose of this study was to report the prediction equation of maximal aerobic power using metabolical responses in submaximal exercise from the Bruce protocol for S Korean adult male, and to validity of these prediction equation. Methods: The subjects were consisted of 255 South Korean adult male. They were joined maximal treadmill exercise testing with Bruce protocol, and the metabolic responses were measured in the end of the first(3 minute) and second stage(6 minute). Measurement items were VO2, VCO2, VE, HR of 3 and 6 minute, time to HR 150bpm and HR 170bpm, HR difference between Bruce protocol 6 and 3 minute, 1,200m running record. To determine the predicted model of VO2max, multiple and simple regression analysis with stepwise methods and enter method were applied. Results: Analyzing with all variables using enter method, the multiple R of total variable model was 0.64(p<.01), SEE was 4.4 ml/kg/min, CV was 10.8%. The multiple R of 3 minutes model was 0.46, SEE was 5.72ml/kg/min, CV was 14.1%. The multiple R of 6 minutes model was 0.46, SEE was 5.7ml/kg/min, CV was 14.2%. The R of 6-3 minutes HR difference model, HR 150, and HR 170 equation were 0.15, SEE were 6.4ml/kg/min, CV were 11.9%. The R of 1,200m running equation was 0.44, SEE was 4.8ml/kg/min, CV was 11.9%. Discussion & Conclusion: Lee, et al.(2012) reported the prediction of maximal aerobic power with general variables and metabolical responses in submaximal exercise for South Korean adult female, and R of total model prediction and general variables model were 0.73 and 0.59(p<.001). In conclusion, the validity of estimation were appeared total, 6 minite, 3 minute, 1,200m running, and 3 HR equation by tunes. With considering usefulness and convenience through the validity of these prediction equations, the prediction equations of maximal aerobic power recommended total model, 6 minute, 3 minute, and 1,200m running.